(untitled) (Journal of the College of Basic Education, 2022)
The study (effectiveness of the functional system for mist fan designs) is subject to the problem of not choosing a mist fan with good specifications, which were of different types and shapes. Functional and aesthetic performance of misting fan designs. The importance of this research came through the establishment of a knowledge base covering the subject of the research to be of benefit to designers and specialists in this field and of benefit to product users, since this study included all aspects of the design fan.